The Effect of Banana Bacteria Wilt on The Socio-Economic Welfare of Farmers in Ruhinda Sub-County Rukungiri District . - Tayebwa, Rameka (Kabale University, 2023)
The study examined the effect of banana bacteria wilt on the socio-economic welfare of farmers in Ruhinda sub-county Rukungiri district. The objectives of the study were to identify the importance of banana production, to assess the impact of banana bacteria wilt on socio- economic welfare of the farmers and to examine the possible measures to control banana bacteria wilt in Ruhinda sub-county Rukungiri district. The researcher employed a descriptive research design and data was collected using interview, observation and questionnaire methods. The study results on importance of banana production in Ruhinda sub-county Rukungiri district indicated that, the highest number of the respondents mentioned food security while the least number of the respondents mentioned source of mulch for maintaining and improving soil fertility. The study went ahead on the impact of banana bacteria wilt on socio- economic welfare of the farmers in Ruhinda sub-county. The highest number of respondents mentioned source of mulch for maintaining and improving soil fertility, the lowest number of respondents mentioned that the disease has led to increased poverty among households and the study continued on possible measures to control banana bacteria wilt in Ruhinda sub-county Rukungiri district, the highest number of respondents mentioned heating garden tools such as hoes, machete, knives and slashers over a fire until the metal is too hot to touch is also effective in killing the bacteria, the lowest number of respondents talked of timely removal of male buds with a forked stick is important in where insect vector that visit the diseased flower parts carry the pathogen. The study recommended that there should be quarantine enforcement by the government agencies to prevent spread of banana bacteria wilt to non-infected areas, there should be policies on the use of clean planting materials and regular inspection/screening for the approved banana nurseries to dispense banana bacteria wilt disease free materials and there should be production of free banana bacteria wilt such as banana tissue culture, train and encourage more banana nurseries producers/tissue culture hardening nurseries to avail clean banana planting materials.